(untitled) (Journal of Engineering Studies and Research, 2022)
Abstract: Using the CAD-CAM-CAE type programs, case studies can be carried out to analyze some industrial tasks that may occur in the realization, manufacture, and operation of certain industrial components, before they are manufactured and put into operation under normal conditions. operation. Computer programs that perform a virtual modeling and an analysis of them based on the finite element method, help reduce launch and production times, control, and review of industrial products, before making the physical model. All this information resulting from simulations with specialized programs will be analyzed in detail, and the design team within the company can take the right measures to improve the final product.